Diversity of T-cell receptors in virus-specific cytotoxic T lymphocytes recognizing three distinct viral epitopes restricted by a single major histocompatibility complex molecule. - Yanagi, Y (1992)
Cytotoxic T lymphocytes (CTL) recognize virus peptide fragments complexed with class I major histocompatibility complex (MHC) molecules on the surface of virus-infected cells. Recognition is mediated by a membrane-bound T-cell receptor (TCR) composed of alpha and beta chains. Studies of the CTL response to lymphocytic choriomeningitis virus (LCMV) in H-2b mice have revealed that three distinct viral epitopes are recognized by CTL of the H-2b haplotype and that all of the three epitopes are restricted by the Db MHC molecule. The immunodominant Db-restricted CTL epitope, located at LCMV glycoprotein amino acids 278 to 286, was earlier noted to be recognized by TCRs that consistently contained V alpha 4 segments but had heterogeneous V beta segments. Here we show that CTL clones recognizing the other two H-2Db-restricted epitopes, LCMV glycoprotein amino acids 34 to 40 and nucleoprotein amino acids 397 to 407 (defined in this study), utilize TCR alpha chains which do not belong to the V alpha 4 subfamily. Hence, usage of V alpha and V beta in the TCRs recognizing peptide fragments from one virus restricted by a single MHC molecule is not sufficiently homogeneous to allow manipulation of the anti-viral CTL response at the level of TCRs. The diversity of anti-viral CTL likely provides the host with a wider option for attacking virus-infected cells and prevents the emergence of virus escape mutants that might arise if TCRs specific for the virus were homogeneous.